A novel homozygous Arg222Trp missense mutation in WNT7A in two sisters with severe Al-Awadi/Raas-Rothschild/Schinzel phocomelia syndrome - Kantaputra P.N. (2014)
Al-Awadi/Raas-Rothschild/Schinzel phocomelia (AARRS) syndrome, a rare autosomal recessive disorder, comprises malformations of upper and lower limbs with severely hypoplastic pelvis and abnormal genitalia. Mutations in WNT7A have been reported as cause of the syndrome. We report on two sisters in a Thai family with short and malformed long bones, absent fibulae, flexion contracture of digits, and a/hypoplastic nails. Fusion between severely malformed femora and slender tibiae has never been reported in patients with WNT7A mutations. Lower limbs were more severely malformed than the upper ones and the pelvis was also severely affected. Multiple fusions of long bones and of the femoral heads to the acetabula were evident. A novel homozygous missense mutation in coding exon 4 of the WNT7A was detected in both affected daughters (c.664C > T) leading to an amino acid exchange from arginine to tryptophan (p.Arg222Trp; R222W). The phenotype is likely to result from an abnormality of all three signaling centers in the developing limb resulting in ventralization with a loss of dorsal structures (aplasia/hypoplasia of nails) a loss of anterior-posterior identity (single distal bones in lower limb without polarity) and an outgrowth defect resulting in distal truncations. © 2010 Wiley-Liss, Inc.